Answer:
C. 2.5×10^-27
Step-by-step explanation:
(2×10^-13)^-2 = 2^-2 × 10^(13×(-2)) = 1/4 × 10^-26
= 0.25 × 10^-26 = 2.5 × 10^-27
___
Your scientific or graphing calculator can compute and display this for you.
Answer:
I think the correct answer is $26,843,545.6
Step-by-step explanation:
I believe you would solve for X like: 3x-10=2x-10.
Zero
There is no solution for these equations as there is no even one point of intersection between them
Answer:
<em><u>8</u></em><em><u>t</u></em><em><u>h</u></em><em><u> </u></em><em><u>t</u></em><em><u>e</u></em><em><u>r</u></em><em><u>m</u></em><em><u>=</u></em><em><u>1</u></em><em><u>0</u></em><em><u>7</u></em>
Step-by-step explanation:
Here the sequence is following the 'fibonacci's sequence of numbers.....
i.e,Tn=T(n-1) +T(n-2), where n>2 but this sequence is not fibonnaci's number , it's not starting with 0, 1,1,2........
so you cannot apply formula to calculate,you have to find 8th term by simple calculation.....
Like here 3rd term is 9 and 1st term is 2
now 3rd term = 2nd term+1st term (sum of previous two terms)
i.e, 9= 2nd term +2
i.e, 2nd term =7
now, 4th term = 3rd +2nd
= 9+7=<u>1</u><u>6</u>
<u>again</u><u>,</u><u> </u> 5th term = 4th +3rd
=16+9=25
again,6th term =5th+4th
=25+16=41
again,7th term=6th+5th
=41+25=66
again,8th term=7th+6th
=66+41=107